2018
DOI: 10.1007/s00520-017-4006-z
|View full text |Cite
|
Sign up to set email alerts
|

Fertility information needs and concerns post-treatment contribute to lowered quality of life among young adult female cancer survivors

Abstract: These preliminary findings suggest that unaddressed fertility information needs, concerns, and decision distress may affect general QOL among post-treatment YAFCS who hope to have children in the future. Future work should identify ways to optimally incorporate fertility counseling and support resources into survivorship care programs, including referrals to reproductive specialists as appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 28 publications
1
89
0
Order By: Relevance
“…As a result of advances in early detection and improvements in treatment, people are living with cancer for longer (Foster, Calman, Richardson, Pimperton, & Nash, ). Although most patients recover well, a significant number of cancer survivors experience a variety of physical and psychosocial concerns that continue even after their treatment has ended (Recklitis & Syrjala, ), including cancer‐related fatigue (Jones et al, ), fertility problems (Benedict et al, ), chronic pain (Selove et al, ), symptoms of depression and anxiety (Philip & Merluzzi, ; Philip, Merluzzi, Zhang, & Heitzmann, ) and fear of cancer recurrence (FCR; Jimenez et al, ). To ensure that cancer survivors’ concerns are appropriately addressed, it is important to continually assess, predict and fulfil their needs.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of advances in early detection and improvements in treatment, people are living with cancer for longer (Foster, Calman, Richardson, Pimperton, & Nash, ). Although most patients recover well, a significant number of cancer survivors experience a variety of physical and psychosocial concerns that continue even after their treatment has ended (Recklitis & Syrjala, ), including cancer‐related fatigue (Jones et al, ), fertility problems (Benedict et al, ), chronic pain (Selove et al, ), symptoms of depression and anxiety (Philip & Merluzzi, ; Philip, Merluzzi, Zhang, & Heitzmann, ) and fear of cancer recurrence (FCR; Jimenez et al, ). To ensure that cancer survivors’ concerns are appropriately addressed, it is important to continually assess, predict and fulfil their needs.…”
Section: Introductionmentioning
confidence: 99%
“…While as many as two‐thirds of RAFCS experience reproductive concerns, their needs for services and information related to their reproductive health and family planning are often unmet . Related reproductive distress, including perceived signs of fertility problems (eg, irregular menstrual function) after cancer, is associated with increased psychological distress and poorer QOL . While specialized counseling by a fertility specialist can be helpful, many RAFCS could benefit from clinical and supportive care to manage their reproductive concerns across the course of survivorship …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Related reproductive distress, including perceived signs of fertility problems (eg, irregular menstrual function) after cancer, is associated with increased psychological distress and poorer QOL. 2,5,[13][14][15] While specialized counseling by a fertility specialist can be helpful, 16,17 many RAFCS could benefit from clinical and supportive care to manage their reproductive concerns across the course of survivorship. 5,13,18-23…”
mentioning
confidence: 99%
“…[2][3][4][5] For example, although the overall proportion of infertile female childhood cancer survivors is 13%, those who underwent total body irradiation have a 28% risk. [6][7][8] Previous studies have shown that potential loss of fertility can be as painful as the cancer diagnosis itself, 9 and for some, the possibility of preserving fertility is instrumental to coping with the burden of cancer treatment. [6][7][8] Previous studies have shown that potential loss of fertility can be as painful as the cancer diagnosis itself, 9 and for some, the possibility of preserving fertility is instrumental to coping with the burden of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%